ACCURACY OF FETAL WEIGHT ESTIMATION ON ULTRASOUND: A COMPARISON BETWEEN SHEPARD AND HADLOCK METHOD (The Research of Medical Science Review, 2025)
Objectives: To compare the accuracy of fetal weight estimation between the Shepard and Hadlock methods. Material and Methods: This study was conducted after obtaining approval from the College of Physicians and Surgeons Pakistan and the Department of Radiology, National Hospital and Medical Centre Lahore. A total of 118 patients were enrolled, all of whom underwent ultrasound examinations. During the procedures, both the Shepard and Hadlock methods were used for fetal weight estimation, ensuring standardized equipment and protocols to reduce variability. The formulas used were the Hadlock II formula (Log10 EFW=1.335-0.0034 ×AC ×FL+0.0316 BPD +0.0457 AC +0.1623 ×FL) and Shepard's formula (Log10 EFW = – 1.7492 + 0.166 BPD + 0.046 AC – 2.646 (AC × BPD)/1,000). The actual fetal weight was obtained post-delivery by direct measurement of the neonate. Ultrasound estimation of fetal weight at term was used to collect data, which was then matched with the actual birth weight of the baby for comparison and statistical analysis was performed using SPSS Version 26. Results: In this study, 118 pregnant women were enrolled. Of the newborns, 68 (57.6%) were male and 50 (42.4%) were female. Regarding gestational age, 70 infants (59.3%) were born between 30 and 35 weeks, while 48 (40.7%) were born between 36 and 40 weeks. The mean estimated fetal weight using Hadlock's formula was 3.3024 kg, compared to 3.2024 kg with Shepard's formula. The mean weight measured post birth via standard weighing scale was 3.1220 kg. Conclusion: It was concluded that both Hadlock's and Shepard's formulas are useful for fetal weight estimation, but Hadlock's formula was more accurate, aligning closely with actual birth weight. This suggests Hadlock's formula may be the preferred choice for more precise fetal weight predictions in clinical settings.